Has the indestructible insect met its match? Velvet ants as prey to bufonid toads. Issue 1 (2nd January 2021) - Mergler, Ciara J.; Gall, Brian G.
Abstract : Velvet ants are a group of parasitoid wasps that are well-known for a suite of defensive traits including bright coloration, a thick exoskeleton, and a painful sting. Previous experiments have demonstrated that while virtually all potential predators avoid velvet ants, toads (family Bufonidae) may be able to prey upon them. We conducted a series of trials to determine whether American ( Anaxyrus americanus ) and Fowler's toads ( Anaxyrus fowleri ) prey upon velvet ants. Toad responses toward velvet ants were variable, ranging between complete avoidance, consumption and regurgitation, and consumption and retention. In total, 12 out of 22 trials resulted in the toads consuming a velvet ant. Of these, velvet ants were either regurgitated unharmed (n = 8) or retained (n = 4). In general, there were no significant differences in responses toward velvet ants between American and Fowler's toads. Due to a rapid prey acquisition and their unique foraging behavior, toads present the most likely predator to velvet ants. Our results indicate that toads have the capacity to consume and retain female velvet ants. However, female velvet ants demonstrate the ability to endure upwards of 20 min inside the stomach of a toad and survive.